Value Chain Management Affecting Business Success: A Case Study of Small and Medium Construction Material Retailer in Roi-Kaen-Sarn-Sin Cluster - Bunnak, Apisit; Prasertsang, Srisunan (Journal of Roi Et Rajabhat University, 2021)
The purposes of this research were to 1) study the level of Value Chain management for medium and small construction material stores, 2) study the level of business success for medium and small construction material stores, 3) compare the business success of medium and small construction material stores by business fundamentals and 4) study Value Chain management affecting on business success for medium and small construction material stores. The sample consisted of 201 medium and small construction material stores in the Roi-Kaen-Sarn-Sin cluster. The instrument was questionnaires. The statistics used were mean, standard deviation, One-way ANOVA, Pearson's simple correlation and multiple regression analysis. The result shows that 1) Value Chain management of medium and small construction material stores in the Roi-Kaen-Sarn-Sin cluster in overall was at a high level. The highest level of an aspect was human resource management. 2) Business success of medium and small construction material stores in the Roi-Kaen-Sarn-Sin cluster in overall was at a high level. The highest level of an aspect was internal process. 3) The medium and small construction material stores in the Roi-Kaen-Sarn-Sin cluster had different locations, the number of employees and duration of operation had different business success. While medium and small construction material stores in the Roi-Kaen-Sarn-Sin cluster had different capital was not different business success. 4) Value Chain management in human resource management, storage, marketing and sales, and after-sales service had a relationship and positive influenced to business success at 0.01 level and procurement had a relationship and positive influenced to business success at 0.05 level. On the other hand, technology development did not had influence to business success.